An Analysis of Errors Made by Students of SMAN 1 Bungku Tengah in Transforming English Active Sentences to Passive Voice - Windasari Windasari; Sudarkam R. Mertosono; Erniwati Erniwati; Jamiluddin Jamluddin (Universitas Tadulako, 2023)
This study aims to describe the most dominant types of errors made by students in transforming active English sentences into passive sentences and to find out the causes of students making errors. The subjects of this study were class XII students of SMAN 1 Bungku Tengah. The samples are 24 students were taken using convenience sampling. This study used qualitative research and data collection using tests items and interviews. The data were identified, classified, and analyzed based on surface strategy taxonomy of Dulay’s theory, namely error of omission with percentage 25,13%, the error of addition with percentage 6,81%, the error of misformation with percentage 65,45% which was established as the dominant error, and error of misordering with percentage 2,62%. Based on the results of interviews, the causes of errorness were, 1) Students did not understand the formula according to tenses, 2) Students were still confused about the use of